# Solving Quadratic Equation with One Unknown

## How to solve a quadratic equation.

The quadratic equation can be expressed as

*a x ^{2} + b x + c = 0 (1)*

which can be solved for the two alternatives of x as

*x _{1,2} = (-b ± (b^{2} - 4 a c)^{1/2}) / (2 a) (2)*

### Example - Solving Quadratic Equation

If

*a = 1*

*b = 6 *

*c = 5*

then the two alternatives for *x* can be calculated as

*x _{1} = (-6 + (6^{2} - 4 1 5)^{1/2}) / (2 1)*

* = -1*

*x _{2} = (-6 - (6^{2} - 4 1 5)^{1/2}) / (2 1) *

* = -5*